Use of Big Book Learning Media in Improving the Reading Ability of Class VII Students at SMPN 1 Tanjung Pura - Fitria Cahaya; Ira Sefi Andini; Melly Br. Bangun; Rodhiatam Mardiah Damanik; Santi Nurhasanah Batubara; Siti Maisaroh (International Journal of Educational Practice and Policy, 2023)
The aim of this research is to improve the reading ability of class VII students at SMPN 1 Tanjung Pura by using the Big Book learning media. The method used in this research is a qualitative method. The research instruments are observation and interview guidelines. The data source for this research is the results of interviews with respondents. The results of observations in this study show that there are problems relating to reading ability in class VII students at SMPN 1 Tanjung Pura, there are 7 students who still 1) don't read fluently, 2) can't spell and hear correctly, 3) there are still those who don't know letters. perfectly, 4) Combining words, 5) Combining words into sentences 6) Sentences into paragraphs. Therefore, the solution offered to this problem is choosing to use big book learning media to change the monotonous way of learning in class by re-teaching the basics of reading and creating special reading learning media that are easy to understand and restore interest in reading for grade 7 students at SMPN 1 Tanjung. Temple. Using the Big Book learning media can help students to be more active in learning activities and facilitate students in understanding teaching materials, especially in learning to read, so that the learning objectives are also achieved with learning media such as the Big Book.